2006
DOI: 10.1634/stemcells.2005-0249
|View full text |Cite
|
Sign up to set email alerts
|

Early Response of Endogenous Adult Neural Progenitor Cells to Acute Spinal Cord Injury in Mice

Abstract: Adult neural progenitor cells (NPCs) are an attractive source for functional replacement in neurodegenerative diseases and traumatic injury to the central nervous system (CNS). It has been shown that transplantation of neural stem cells or NPCs into the lesioned region partially restores CNS function. However, the capacity of endogenous NPCs in replacement of neuronal cell loss and functional recovery of spinal cord injury (SCI) is apparently poor. Furthermore, the temporal and spatial response of endogenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 45 publications
(75 reference statements)
5
84
0
Order By: Relevance
“…As a further clue supporting the hypothesis that seladin-1 is a predominant product of stem cells, we also detected a high amount of seladin-1 mRNA in the human adult hippocampus and spinal cord, which have been shown to contain neural stem cells with neurogenic activity [8][9][10] (Table 1). The level of seladin-1 mRNA in these regions was rather close to the amount of transcript detected in the adrenal cortex, one of the tissues in which the highest levels of transcription had been detected [1].…”
Section: Expression and Activity Of Seladin-1 In Hmsc And In Hmsc-nsupporting
confidence: 80%
See 2 more Smart Citations
“…As a further clue supporting the hypothesis that seladin-1 is a predominant product of stem cells, we also detected a high amount of seladin-1 mRNA in the human adult hippocampus and spinal cord, which have been shown to contain neural stem cells with neurogenic activity [8][9][10] (Table 1). The level of seladin-1 mRNA in these regions was rather close to the amount of transcript detected in the adrenal cortex, one of the tissues in which the highest levels of transcription had been detected [1].…”
Section: Expression and Activity Of Seladin-1 In Hmsc And In Hmsc-nsupporting
confidence: 80%
“…With regard to this point, it is worth mentioning that, according to the findings of Greeve et al [1], we detected high levels of seladin-1 transcript in the adult hippocampus, a well-known neurogenic brain region [8], and which is one of the areas affected in AD. Similarly, a high amount of seladin-1 mRNA was found in the spinal cord, in which stem cells with neurogenic properties have been recently described [9,10]. Alternatively, our findings might indicate a modification of the neurogenic properties of the adult brain as a consequence of neuronal damage and therefore of AD itself.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Tracing of nestin positive neural progenitors resident in the adult spinal cord has revealed that these cells proliferate and differentiate into neurons at the lesion area following dorsal compression injury [19]. Focal ischemia was shown to increase the normal rate of neurogenesis in the cortex and hippocampus [20,21], and the results could be enhanced by exogenous delivery of growth factors [21].…”
Section: Injury-induced Recruitment Of Endogenous Nscsmentioning
confidence: 99%
“…Ependymal cells adjacent to the spinal canal proliferate extensively upon spinal cord injuries (16,17). Proliferation of adult brain LV ependymal cells (18) can also be detected after a stroke.…”
mentioning
confidence: 99%